Modelling and simulation of fluid flow through a circular cylinder with high reynolds number: a COMSOL multiphysics study - A. Memon, Abid; Memon, M. Asif; Bhatti, Kaleemullah; Jacob, Kavikumar; Sitthiwirattham, Thanin; Promsakon, Chanon; Khan, Ilyas (Hindawi, 2022)
In this study, we intend to investigate the steady-state and laminar ow of a viscous uid through a circular cylinder xed between two parallel plates keeping the aspect ratio of 1 : 5 from cylinder radius to height of the channel. e two-dimensional, incompressible uid ow problem has been simulated using COMSOL Multiphysics 5.4 which implements nite element’s procedure. e ow pattern will be investigated by using the Reynolds number from 100 to 1000. e reattachment length formed at the back of the cylinder and drag force when the uid comes to strike with the front surface of the cylinder is expressed in terms of Reynolds numbers. We propose to calculate the velocity and the pressure before and after the cylinder. For this purpose, twoline graphs before and after the cylinder will be drawn to check the impact of cylinder on both velocity and pressure. It was found that the percentage change in the velocity as well as pressure before to after the cylinder is changing their behaviours at Re 700. e study is important because the empirical equations between the vortex’s lengths formed along the cylinder using the linear regression process obtained in this study may be used for future implementation